Workshop “Life in the Cosmos - Beyond the blind spots” - Tozzi, Paolo (Il Colle di Galileo, 2025)
Astrobiology has made remarkable progress in the last 30 years. From the discovery of exoplanets to the development of atmospheric characterisation techniques and relevant in situ missions to objects in the solar system, there has been an explosion in studies of where, when and how life might form (and thrive) in the Universe. However, by its nature, Astrobiology is a new kind of wildly interdisciplinary (or even transdisciplinary) science requiring extensive collaborations across fields as diverse as geology, planetary science, biology, ecology and even anthropology and history. In this workshop (perhaps the first in a series), we focus on progress in the field with a focus on the “blind spots” that currently exist. Given the progress being made, we ask what kinds of perspectives are needed and how these blind spots might be addressed. The organisers aim to build new, interdisciplinary networks of collaboration to address the most exciting and challenging issues surr ounding life in the cosmos.